The Effectivenes of Red Rice to Decrease Total Cholesterol in Type 2 DM Patients - Wydi Ulfa Pradini; Ancah Caesarina Novi Marchianti; Rini Riyanti (Faculty of Medicine, University of Jember, 2017)
Diabetes mellitus (DM) is a group of metabolic diseases with hyperglycemia characteristic that happens because anomaly of insulin secretion or insulin activity. Insulin deficiency in type 2 DM caused dislipidemia. Red rice are contain fiber, essential fatty acid and Gamma Amino Butiric Acid (GABA). This research intended to know the effectiveness of red rice to decrease total cholesterol levels of patient with type 2 DM. Clinical test with quasi experimental and research design non randomized control-group pretest-postest design was used for the research method. Total samples of this research are 36 samples. The treated group was given the red rice during 6 days on breakfast and dinner, while the control group did not have any intervention. The research showed that average cholesterol levels in the beginning and finale of treated group was 235,69 mg/dL and 198,56 mg/dL, while average cholesterol levels in the beginning and finale of control group was 235,72 mg/dL and 256,50 mg/dL. From this research, red rice has effective to decrease total cholesterol levels of patients with type 2 DM.Keywords: Diabetes mellitus, Red Rice, Cholesterol total levels